Digital strategy - Hanlon, Annmarie (Henry Stewart Talks, 2016)
RACE planning tool, Acquire, convert, retail, SWOT, Website analysis tools, Digital marketing toolbox, Managing social media, Effective emails, Community building, The 7Ps and online value propositions, Customer personas, SMART objectives, The 5Ms of needed resources